Cardiovascular Risk Factors Among Young People in Haiti: Implications for Low-Income Countries - Lindsey K. Reif; Vanessa Rouzier; Lily D. Yan; Shalom Sabwa; Genevieve Hilaire; Marie Jean Pierre; Rose Cardelle Riche; Robert Peck; Anju Ogyu; Rodney Sufra; Jean W. Pape; Daniel W. Fitzgerald; et al. (Global Heart)
Introduction: Cardiovascular disease (CVD) is a leading cause of global mortality with >80% of the burden in low-income countries. We investigate population-based estimates of CVD risk factors among young people ages 18–30 in Haiti and provide insights for CVD prevention. Methods: This is a cross-sectional study within the Haiti Cardiovascular Cohort Study. CVD risk factors include: high blood pressure (BP), dyslipidemia, kidney disease, overweight and obese, and health behaviors. Multivariate logistic regression assessed associated independent factors. Results: Among 957 participants ages 18–30 years, 23.5% had high BP (95%CI: 20.9%–26.3%), 34.9% had dyslipidemia (95%CI: 31.8%–38.1%), 6.4% had kidney disease (95%CI: 4.8%–8.4%), 16.5% were overweight (95%CI: 14.2%–19.0%), and 6.8% were obese (95%CI: 5.3%–8.6%). More males had high BP (33.6% vs. 14.0%; p < 0.001) and more females had dyslipidemia (45.1% vs. 23.9% p < 0.001). Overweight and obese participants had higher odds of high BP (aOR: 2.05, 95%CI: [1.31–3.19]; aOR 2.15, 95%CI [1.11–4.04]) and dyslipidemia (aOR: 1.70, 95%CI [1.15–2.50]); aOR 2.82, 95%CI [1.63–4.98]) compared to those with normal BMI. Participants ages 25–30 had higher odds of high BP (aOR: 1.58, 95%CI: [1.14–2.18]) and dyslipidemia (aOR: 1.81, 95%CI: [1.35–2.43]) compared to participants ages 18–24. Discussion: Prevalence of high BP and dyslipidemia are alarmingly high in Haitian young adults, with higher rates of dyslipidemia in women and elevated BP in men. These data provide evidence for routine CVD screening in young people as early as 18 years and underscore the need to identify modifiable drivers of early-onset CVD.